Introduction of multiple disulfide bonds increases the thermostability of transglutaminase - Takuto Ono; Kazutoshi Takahashi; Yoshinori Hirao; Yasuhiro Mihara; Isao Abe; Ayaka Shirasawa; Masayuki Sugiki (Scientific Reports)
Abstract Microbial transglutaminase (MTG) is an enzyme that catalyzes the cross-linking of glutamine and lysine residues in proteins. Because of its ability to modify proteins, MTG has various applications in the medical and food industries. Most studies have aimed to enhance the thermal stability of MTG by focusing only on point mutations. Introducing a disulfide (S-S) bond in the N-terminal region has been found to be effective, whereas S-S bonds in other regions were considered ineffective. Therefore, this study aimed to evaluate the impact of introducing an additional S-S bond on the thermal stability of an MTG mutant. We found that adding S-S bonds to regions other than the N-terminal, in conjunction with the N-terminal S-S bond, significantly enhanced thermal stability. This finding demonstrates the importance of reinforcing the weakest part of the protein first, followed by strengthening other regions for optimal thermal stability. The MTG variant with two S-S bonds retained its catalytic activity and substrate specificity towards protein substrates, making it a promising candidate for industrial applications. Thus, introducing S-S bonds could be an effective strategy to increase thermal stability of MTG and other industrial enzymes, thereby contributing to their potential industrial applications.